KOMBINASI SPEKTROFOTOMETRI ULTRAVIOLET DAN KALIBRASI MULTIVARIAT UNTUK ANALISIS METAMPIRON, VITAMIN B1, DAN VITAMIN B6 SECARA SIMULTAN TANPA PEMISAHAN - , Chusnul Chotimah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Generaly, analysis of two or more active substances is carried out using chromatographic tehniques, which need a long time and high costs, making it less suitable to be used in routine testing in quality control of drug. Due to the increasing number of multicomponent drug products, it is necessary to develop a quick, simple, safe and low cost analytical method. By the development of computer software and multivariate analysis, the uv-vis spectrophotometric method is widely used for the analysis of multicomponent compounds simultaneously. The aim of this study is to develop uv-vis spectrophotometry coupled with multivariate calibration of partial least square (PLS) for quantitative analysis of methampyron (MET), thiamin (Vit B1) and pyridoxin (vit B6) in the presence of cyanocobalamine without separation step. The study of uv-vis spectrophotometry in combination with multivariate calibration is conducted in three phases, namely the calibration, validation and samples assay. The evaluation of calibration model was based on the coefficient of determination (R2), root mean square error of calibration (RMSEC), root mean square error of cross validation (RMSECV), root mean square error of prediction (RMSEP) and the predicted residual sum of square (PRESS). The HPLC methods used for comparison method. The results showed that uv spectrophotometry combined with PLS multivariate calibration can be used for quantitative analysis of drugs. The coefficient of determination (R2) for the relationship between actual values and predicted values for all studied drugs was higher than 0,99 indicating good accuracy. The RMSEC, RMSECV, RMSEP and PRESS values obtained were relatively low indicating good precision. The level of MET, Vit B1 and Vit B6 obtained using UV spectrophotometry combination with PLS are 96.27 ± 0.38 %, 100.48 ± 1.82 % and 98.45 ± 1.66 % respectively, and those by HPLC are 96.06 ± 0.76 %, 99.35 ± 1.56 % and 98.96 ± 0.67 %, for MET, Vit B1 and Vit B6 respectively. The accuracy and presision results of developed method showed no significant difference compared to those obtained by HPLC. The developed method was succesfully used for analysis of methampyron, thiamin and pyridoxin in tablet dosage form.